An unusual cause of tenosynovitis by group B streptococcus in the immunocompromised patient: a case report - Muthanna, Abdulrahman; Aziz, Nur Afiza; Mohd Desa, Mohd Nasir; Dzaraly, Nurul Diana; Zainal Baharin, Nurul Hana; Azmai, Mohammad Noor Amal; Nordin, Syafinaz Amin (Universiti Putra Malaysia Press, 2022)
This case report describes a 49-year-old immunocompromised woman with tenosynovitis of the left middle finger caused by Group B Streptococcus (GBS). She claimed that a fishbone picked over her left middle finger. An orthopaedic surgeon operated for incision and drainage of pus discharge, wound debridement of the left middle finger and A1 and A2 pulley release. Treatment was initiated with parenteral cefepime three times per day given the growth of mixed Enterobacter species on the culture media and continued with oral cefuroxime twice daily upon discharge for one week. Unfortunately, during the orthopaedic clinic follow-up, the wound was unclean with a slough and skin necrotic patch. Therefore, Ray’s amputation of the left middle finger proceeded. This case contributes to further investigation of the GBS tenosynovitis due to the rise in GBS invasive infections and shows the importance of early diagnosing and initiating treatment with antibiotics that are effective against this pathogen.